CAPITAL BUDGETING: A CRITICAL MODEL FOR STRATEGIC DECISION MAKING IN MANUFACTURING COMPANIES IN CROSS RIVER STATE, NIGERIA. - UDOKA, CHRIS O.; BASSEY, IBOR I.; ARIKPO, OKA FELIX (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
This study examined capital budgeting as a critical model for strategic planning in manufacturing companies in Cross River State, Nigeria. The objectives of the study were to examine the degree of relationship between the adoption of NPV model and the return on investment in manufacturing firms in Nigeria; to investigate the extent to which capital budgeting models could influence strategic planning in manufacturing firms in Nigeria. In order to achieve these objectives, three research hypotheses were tested at 5% level of significance. The survey research design was adopted and a well structured questionnaire was constructed to gather data for the study. The questionnaire was administered on 108 respondents comprising the management and operational staff of quoted firms in Cross River State. The Pearson product moment correlation statistical technique was applied. Findings resulting from the test revealed that capital budgeting model influenced significantly strategic planning and managerial decisions. The NPV model was found to be positively correlated with manufacturing firms returns on investments. Based on these findings, it was recommended that corporate planners should train management and line staff on the right application of capital budgeting models. Managers were encouraged to constantly appraise investments alternatives weigh in the results of capital budgeting estimation and their strategic planning process.